Food aid: Pros and cons - Hans W. Singer (Intereconomics, 1988)
Extreme poverty, drought and famine continue to afflict people in many parts of the world. Food aid has occupied a central role in the response to these problems, and there have been notable successes, yet there is doubt and criticism about the appropriateness of food aid. Is food aid doing more harm than good?
Keywords: 330; North-South Relations